Evaluation of Airway Resistance in Children with Juvenile Idiopathic Arthritis - KARAKURT, SAİT; ÇELİKEL, TURGAY HÜSEYİN (MARY ANN LIEBERT, INC, 2014)
Background: Pneumonitis, pleuritis, and pulmonary interstitial infiltration have been described in patients with juvenile idiopathic arthritis (JIA). However, the pulmonary involvement of JIA is not often clinically apparent. There are few studies based on pulmonary function in children having only a diagnosis of JIA. The aim of the present study is to determine whether children with JIA have airway resistance and flow impairments measured by easily applied interrupter technique. Method: We performed interrupter resistance (Rint) measurements in children with JIA and in healthy control subjects who had no respiratory symptoms or diseases. Results: Fifty-eight children with the diagnosis of JIA (Mean age = 12.5 +/- 2.75 years; range 7-17 years) and 33 healthy subjects (Mean age = 11.8 +/- 2.62 years; range 6-16 years) were included in the study. The mean value of tidal peak flow during expiration measured by the interrupter technique was significantly lower in the JIA study group (0.73 +/- 0.11 L/s) compared to the healthy control group (0.79 +/- 0.08 L/s; p = 0.01). Rint values measured during inspiration (Rint(insp)) and during expiration (Rint(exp)) were higher in the JIA study group (Rint(insp) = 0.28 +/- 0.16 Kpa/L/s; Rint(exp) = 0.30 +/- 0.50 Kpa/L/s) compared to the healthy control group (Rint(insp) = 0.26 +/- 0.11 Kpa/L/s; Rint(exp) = 0.23 +/- 0.08 Kpa/L/s; p > 0.05). There was also a positive correlation between C-reactive protein level and median expiratory interrupter resistance (Rint(exp); r = 0.50, p = 0.005). Conclusion: The interrupter technique is a noninvasive and feasible technique and can be used to assess airway abnormalities in children with JIA who cannot successfully complete spirometry.
Keywords: INTERRUPTER TECHNIQUE; RHEUMATOID-ARTHRITIS; PULMONARY-FUNCTION; METHOTREXATE THERAPY; PRESCHOOL-CHILDREN; REFERENCE VALUES; LUNG-FUNCTION; YOUNG-CHILDREN; DISEASE; CLASSIFICATION